TEACHING MODERATION THROUGH STORYTELLING FOR CHILDHOOD LEARNERS USING ETHNIC PUPPETS - Nanik Shobikah (Raheema, 2021)
This article is aimed to introduce the media development in teaching English storytelling using puppets. Puppets are modified into ethnic puppets in order to teaching moderation for childhood learners. Teaching moderation is aimed to give the childhood learners an experience of learning process, self-awareness, and automaticity of Indonesia as Bhinneka Tunggal Ika (United in Diversity). This paper using qualitative design, library research through intensive reading, intensive writing, and collecting the data from Mendeley Reference Manager, Google Scholar, and Google Book. The source of data are journals, books, articles, documents and other references related to the research focus. The research findings found that the purposes of teaching moderation through storytelling using ethnic puppets is to teach harmony in living together with many ethnics in Indonesia in a simple way by telling a story containing moral values and introducing ethnic puppets wearing ethnic clothes as the characters of the story. In teaching moderation, teacher prepares some steps in providing the ethnic puppets. First, decide the story and its moral values. Second, making the ethnic puppets. Third, practicing storytelling. Fourth, retelling the story.